XRF-data (Ca and Ti) of seismites and non-seismic induced deposits from the Dead Sea center from sediment core ICDP 5017-1 - Yin Lu; Jasper Moernaut; Revital Bookman; Nicolas D Waldmann; Nadav Wetzler; Amotz Agnon; Shmuel Marco; Ian G Alsop; Michael Strasser; Aurélia Hubert-Ferrari (PANGAEA, 2020)
During 2010-2011, the ICDP recovered a 457 m long Core 5017-1 from ~300 m of water depth in the center of the Dead Sea. The cored sequence is characterized by alternating laminae of white aragonite and dark detritus (aad), gypsum, and halite. U-Th and 14C dating constrain the age of the core to 220-0 ka. The surface of the archived half of the core was scanned with the ITRAX core scanner at a resolution of 1 mm, an exposure time of 1 s, and a Chromium tube at 30 kV voltage and 30 mA current at the GFZ. Here we use the XRF data (Ca and Ti) characterizing the features of seismites and non-seismic induced deposits (gypsum, halite, mud, and aragonite-detritus laminae) from the Dead Sea center. This high-resolution dataset allows us to get a better understanding of seismogenic sedimentary processes in the Quaternary Dead Sea.